Comparison of 25‐hydroxyvitamin D concentration in chimpanzee dried blood spots and serum. (22nd May 2020) - Moittié, Sophie; Graham, Peter A.; Barlow, Nicola; Dobbs, Phillipa; Liptovszky, Matyas; Redrobe, Sharon; White, Kate
Abstract: Background: Dried blood spots (DBS) are used in human medicine to measure total 25‐hydroxyvitamin D (25‐OHD) in the blood. However, this easy and affordable sampling technique has not been evaluated in primates to measure vitamin D concentrations. Objectives: We aimed to compare 25‐OHD measurements in chimpanzee serum at two different laboratories and determine the precision and accuracy of the DBS method by comparing DBS and serum results. Methods: Blood samples from 17 captive chimpanzees were collected, and 25‐OHD3 and 25‐OHD2 were measured in serum at two accredited laboratories using liquid chromatography‐tandem mass spectrometry. The same analytes were measured on DBS cards, and results were compared with that of serum. Data were assessed using the Spearman correlation, Deming regression, and Bland‐Altman analyses. Results: The correlation coefficient between the two measurements in serum was r s = .51 ( P = .04), and the mean bias was −1.25 ± 14.83. When comparing 25‐OHD concentrations measured in DBS and serum at the same laboratory, the r s was 0.7 ( P = .002), and the mean bias was 1.42 ± 14.58. Estimated intra‐assay and inter‐assay coefficients of variation for DBS results were 6% and 12.6%, respectively. Conclusions: Although substantial analytical variability was found in 25‐OHD measurements regardless of the sample type, the identification of both constant and proportional error and wider limits of agreement with the DBS technique makes the interpretation of DBS results challenging, especially for values close to clinical cut‐off points. The DBS and serum methods were not interchangeable, and further studies are needed to validate DBS samples for vitamin D measurements in chimpanzees.